Practicing hope : a handbook for building HIV and AIDS competence in the churches - Parry, Sue. (Geneva 2,Switzerland World council of churches publications, 2013)
"Almost 35 years after the advent of HIV and AIDS, churches, church bodies, and church leaders are developing competence in handling the enormous personal, communal, cultural, and religious dimensions of the epidemic. Yet, the challenge is ongoing and global. While the rate of new infections is declining in Africa, it is on the rise in Eastern Europe, Asia, and the Middle East. In this handbook, Dr. Sue Parry - a physician in Zimbabwe with broad experience in the provision of clinical care, and whose Beacons of Hope provided a breakthrough in helping African churches and other churches gain HIV competence - gathers the clinical and pastoral knowledge of a generation for pastoral caregivers, seminary educators, and professionals in ministry. Providing a sophisticated and comprehensive framework, the book also demonstrates and facilitates the vital role that churches can play in addressing, not just the clinical, but also the deeper cultural and religious dimension of the HIV epidemic. Parry's practical and perceptive guide to mainstreaming HIV competence enables Christians and Christian churches to not merely envision hope, but to also practice it"--
Includes bibliographical references (pages 171-182).
Keywords: AIDS (Disease) -- Religious aspects -- Christianity; AIDS (Disease) -- Patients -- Pastoral counseling of; HIV infections -- Religious aspects -- Christianity; HIV-positive persons -- Pastoral counseling of; Church work with the sick